2022
DOI: 10.1007/s40267-022-00893-y
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions from two COVID-19 vaccines reported in Saudi Arabia

Abstract: Background Several reports have been published about the impact of coronavirus disease 2019 (COVID-19) vaccines on human health, and each vaccine has a different safety and efficacy profile. The aim of this study was to reveal the nature and classification of reported adverse drug reactions (ADRs) of the two COVID-19 vaccines (tozinameran and ChAdOx1) among citizens and residents living in Saudi Arabia, and show possible differences between the two vaccines and the differences between each batch o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The fatigue and fever symptoms were found to be associated with Oxford-AstraZeneca administration and these results are aligned with other studies [12,14,15,17]. Our analysis revealed a high proportion of side effects among AstraZeneca recipients, and these findings are consistent with previous investigations [12,14].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The fatigue and fever symptoms were found to be associated with Oxford-AstraZeneca administration and these results are aligned with other studies [12,14,15,17]. Our analysis revealed a high proportion of side effects among AstraZeneca recipients, and these findings are consistent with previous investigations [12,14].…”
Section: Discussionsupporting
confidence: 92%
“…In this context, surveillance of vaccine safety is of paramount importance to mitigate the fear of vaccinations among the masses. On the other hand, the real-world data (RWD) on pharmacovigilance of the COVID-19 vaccine in Saudi Arabia are primarily based on the reporting from healthcare professionals [12], adolescents [13], the general population [14][15][16], and recipients of one type of vaccine [17,18]. This study aimed to investigate the short-term side effects of the administration of the COVID-19 vaccine doses among the general population in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Saudi Arabia which included 7768 Vaxzevria vaccinees and 5100 receiving Comirnaty, no case of anaphylaxis was reported. However, authors reported that mild/ moderate allergic reactions occurred at a frequency of 4.5% for the Vaxzevria vaccine and 7.2% for Comirnaty [22].…”
Section: Evidence From Post-marketing Observational Studiesmentioning
confidence: 99%
“…must be reported. ADRs related to herbal and traditional medications [ 66 , 67 ], cosmetics [ 34 , 68 ], vaccines [ 69 , 70 ], newly approved drugs [ 71 ], and unknown ADRs to old drugs [ 72 , 73 ] are well recognized. However, only 51% of HCPs considered the mandatory reporting of all ADRs.…”
Section: Discussionmentioning
confidence: 99%